Physical Characteristics of Ice Cream with the Addition of Butterfly Pea Flower Extract and Porang Glucomannan Flour (Amorphophallus muelleri) - Qisthina, Yaumil; Asben, Alfi; Anggraini, Tuty (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study aims to determine the interaction between the use of various butterfly pea flower extracts with the concentration of porang glucomannan flour on the physical characteristics of ice cream. This study employed a Factorial Completely Randomised Design (CRD) with two factors: butterfly pea flower extract and different concentrations of porang glucomannan flour. Each treatment was repeated 3 times. Data analysis was conducted using Analysis of Variance (ANOVA), followed by Duncan's New Multiple Range Test (DMRT) at a significance level of 5%. There is an interaction between variations in various different butterfly pea flower extracts and the concentration of porang glucomannan flour on the Hue and viscosity of ice cream. Variations in various butterfly pea flower extracts significantly affect the melting power, and viscosity of ice cream. The concentration of porang glucomannan flour significantly affects the Hue, melting power, and viscosity of ice cream. The best product is the treatment with the addition of 35% butterfly pea flower extract and 0.3% porang glucomannan flour, characterised by an average Hue value of 253.56°, an overrun of 36.37%, a melting power of 37.67 minutes, and a viscosity of 62 Cp. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production